2021
DOI: 10.3389/fcell.2021.741368
|View full text |Cite
|
Sign up to set email alerts
|

Shaping the Microglia in Retinal Degenerative Diseases Using Stem Cell Therapy: Practice and Prospects

Abstract: Retinal degenerative disease (RDD) refers to a group of diseases with retinal degeneration that cause vision loss and affect people’s daily lives. Various therapies have been proposed, among which stem cell therapy (SCT) holds great promise for the treatment of RDDs. Microglia are immune cells in the retina that have two activation phenotypes, namely, pro-inflammatory M1 and anti-inflammatory M2 phenotypes. These cells play an important role in the pathological progression of RDDs, especially in terms of retin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 191 publications
0
5
0
Order By: Relevance
“…A shift of immune cells towards proinflammatory phenotypes is evidenced by autopsy studies ( 112 114 ) and peripheral blood samples collected from glaucoma patients ( 115 , 116 ). As a result, researchers have proposed immunomodulatory therapy by applying regulatory exosomes, which are commonly collected from M2 microglia and stem cells, to shape microglia phenotypes (see part 4) ( 117 ).…”
Section: Role Of Microglia-derived Exosomes In the Spreading And Modu...mentioning
confidence: 99%
“…A shift of immune cells towards proinflammatory phenotypes is evidenced by autopsy studies ( 112 114 ) and peripheral blood samples collected from glaucoma patients ( 115 , 116 ). As a result, researchers have proposed immunomodulatory therapy by applying regulatory exosomes, which are commonly collected from M2 microglia and stem cells, to shape microglia phenotypes (see part 4) ( 117 ).…”
Section: Role Of Microglia-derived Exosomes In the Spreading And Modu...mentioning
confidence: 99%
“…Due to their various functions, it is believed that exosomes could potentially be used for treating ocular diseases. To date, various studies have been conducted on the use of exosomes to treat ocular diseases, involving exosomes derived from mesenchymal stem cells (MSCs), ESCs, and neural progenitor cells [ 195 , 203 ]. A new study published recently by Zhou et al was the first to show that ROs produced from human iPSCs release exosomes and microvesicles with genetic cargo.…”
Section: Importance Of Extracellular Vesicles Secreted By Retinal And...mentioning
confidence: 99%
“…The advanced stages of RD is characterized by the massive loss of retinal neurons, therefore, the direct use of stem cells to replace the injured neurons is also a research hotspot (Nazari et al, 2015). A number of studies have shown that stem cells transplanted into the damaged retina can differentiate into retinal cells, and even integrate into the retina to restore the visual function of RD (Gagliardi et al, 2019;Jin et al, 2021).…”
Section: Stem Cell Integrationmentioning
confidence: 99%